Comparative Study for the Early Detection of the most Important Factors Leading to Preeclampsia - Dawood Al-Marsuomy, Aseel Mubdir; Subhi Fadhel, Mustafa Mohammed (Journal of Economics and Administrative Sciences, 2021)
The aim of this research is to determine the most important and main factors that lead to Preeclampsia. It is also about finding suitable solutions to eradicate these factors and avoid them in order to prevent getting Preeclampsia. To achieve this, a case study sample of (40) patients from Medical City - Oncology Teaching Hospital was used to collect data by a questionnaire which contained (17) reasons to be investigated. The statistical package (SPSS) was used to compare the results of the data analysis through two methods (Radial Bases Function Network) and (Factorial Analysis). Important results were obtained, the two methods determined the same factors that could represent the direct reason which causes Preeclampsia. But the first method of analysis was more precise and accurate in identifying these factors. Concerning both methods, the focus was on the factors of (following a good nutritious diet, a dysfunction in the placenta, and suffer from high blood press before pregnancy) had a major effect on their potential susceptibility to Preeclampsia.